The prevalence and 6-year incidence of myopic tessellation in a Chinese rural adult population: the Handan Eye Study - Caixia Lin; Jian Wu; Kai Cao; Bingsong Wang; Yuxin Fang; Ohno-Matsui Kyoko; Yunyun Sun; Jie Hao; Lixia Ma; Ye Zhang; Qing Zhang; Ningli Wang; et al. (BMC Ophthalmology, 2025)
Abstract Purpose To describe the prevalence and the cumulative 6-year incidence of fundus tessellation in a rural Chinese adult population. Methods The Handan Eye Study was a population-based longitudinal study, with 6830 eligible subjects included in the baseline period, and 5394 subjects (follow-up rate: 85.3%) took part in the follow-up study. Participants had detailed eye examinations and physical examinations; a detailed questionnaire was also well administered. Fundus tessellation was defined as well-defined choroidal vessels that can be observed clearly around the fovea as well as around the arcade vessels. Results Among 6830 subjects who participated in the baseline study, the prevalence of fundus tessellation was 9.89% (95%CI: 9.22-10.58%). The prevalence of fundus tessellation increased with age; that of subjects aged younger than 50 years and those aged 50 years or older was 2.5% and 14.5%, respectively. Six years later, the cumulative 6-year incidence of fundus tessellation was 1.21% (95%CI: 1.03-1.40%). Similarly, the incidence of fundus tessellation also increased with age; that of participants aged younger than 50 years and those aged 50 years or older was 0.20% and 1.86%, respectively. The progression rate of fundus tessellation in those with fundus tessellation at baseline was 1.5% (95% CI: 0.82%, 2.38%). By multivariable analysis, subjects being older (OR: 1.079, P < 0.001) and havingβ-parapapillary atrophy at baseline (OR: 2.657, P = 0.002) were associated with a higher risk of incidence of fundus tessellation. Conclusions The prevalence and 6-year incidence of fundus tessellation were 9.89% and 1.21% in rural Chinese adults aged 30 + years, respectively. The progression rate in participants with fundus tessellation indicates the importance of regular follow-up for these patients.